Non-linear indices of heart rate variability during endodontic treatment - Ramos Santana, Milana Drumond; Pita-Neto, Ivo Cavalcante; Martiniano, Eli Carlos; Lucas Monteiro, Larissa Raylane; Souza Ramos, Jose Lucas; Garner, David M.; Valenti, Vitor Engacia [UNESP]; Abreu, Luiz Carlos de (Sociedade Brasileira De Pesquisa Odontologica, 2016)
Dental treatment promotes psychosomatic change that can influence the procedure and compromise the general well-being of the patient. In this context, it highlights the importance of evaluating the function of the autonomic nervous system in individuals undergoing endodontic treatment. Thus, this manuscript aimed to analyse cardiac autonomic modulation, through non-linear indices of heart rate variability (HRV) during endodontic treatment. Analysis of 50 subjects of either sex aged between 18 and 40 years diagnosed with irreversible pulp necrosis of lower molars undergoing endodontic treatment was undertaken. We carried out fractal and symbolic analysis of HRV, which was recorded in the first session of the endodontic treatment at four intervals: T1: 0-10 min before the onset of the treatment session; T2: 0-10 min after the application of anaesthesia; T3: throughout the period of treatment; and T4: 0-30 min after the end of the treatment session. There was reduction of alpha 1 in T2 compared to T1 and T4 (p < 0.0001). The alpha 2 index also reduced in T2 compared to T3 (p = 0.0035). There was an increase in the alpha 1/alpha 2 ratio in T4 compared to T2 and T3 (p = 0.0003). It was found that 0V% was significantly lower in T2 (p = 0.002), while 2UV% was significantly higher (p < 0.0001) when compared to other points in time. In conclusion, HRV is reduced during endodontic treatment, and after applying local anaesthetic the parasympathetic component of HRV increases. These data indicate that endodontic treatment acutely overcharges the heart, supporting the stress involved in this situation.
Keywords: Endodontics; Autonomic Nervous System; Cardiovascular Physiology; Heart Rate Variability